Parametric and catalytic study of nickel-ion mixed selenides as oxygen evolution reaction electrocatalyst in an alkaline electrolyzer - Ortenero, Joseph R.; Ocon, Joey D. (Quezon City College of Engineering, University of the Philippines Diliman, 2019)
Transition metal chalcogenides have been employed to catalyze the sluggish kinetics of oxygen evolution reaction (OER) in water splitting. However, transition metal selenides have not received similar interest as other types of chalcogenides such as oxides. Here, we report a porous selenium-rich nickel-iron mixed synthesized via electrodeposition and investigated its electrocatalytic activity as anodic material for OER. A parametric study on Ni-Fe mixed selenide co-deposition was investigated via a rotating disk electrode (RDE). The co-deposition of Ni, Fe and Se is limited by diffusion of SE4? ions in the form of H2SeO3 on the electrode surface. It is proposed that Ni-Fe mixed selenide phases are formed through the reactions: H2SeO3 + Ni²? + 4H? + 6e¯ -> NiSe + 3H2O and ?H2SeO3+ Fe²?+ + 4?H? + (4? + 2)e¯-> FeSe? + 3?H2O. The activity of synthesized catalyst was measured through an electrochemical workstation. Ni-Fe selenide films with ~7 at.%Fe showed the lowest OER overpotential of 318mV at 10 mA cm-², low onset potential of 260 mV at 0.5 mA cm-² and a low Tafel slope of 58.3 mV dec-¹. In contrast, NiSe films with similar Ni and Se content showed overpotential of 395mV and 386mV at 10mA cm-², respectively. These films also registered higher Tafel slopes of 82.5 mV dec-1 and 81.8 mV dec-¹ respectively. Linear sweep voltammetry (LSV), cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), SEM-EDX, XRD, XRF, XPS and Raman spectroscopy demonstrated evidence of Ni-Fe mixed selenides. This work elucidated and electrocatalytic activity of porous Se-rich Ni-Fe mixed selenides as anodic electrocatalyst for water splitting in alkaline s
Thesis (Doctor of Philosophy in Chemical Engineering)--University of the Philippines Diliman
Keywords: Water -- Elect; Chalco; Oxygen evolution r; Alkaline elect; Water sp; Electrodep